2022
DOI: 10.3390/v14030539
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Vaccines during Pregnancy and Breastfeeding: A Systematic Review of Maternal and Neonatal Outcomes

Abstract: PubMed, Cochrane Library, and the Education Resources Information Center (ERIC) were searched up to 27 October 2021. The primary outcome was to estimate how many pregnant and lactating women were reported to be vaccinated and had available maternal and neonatal outcomes. (3) Results: Forty-five studies sourcing data of 74,908 pregnant women and 5098 lactating women who received COVID-19 vaccination were considered as eligible. No major side-effects were reported, especially during the second and third trimeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 69 publications
(89 reference statements)
2
22
0
2
Order By: Relevance
“…In the United States, maternal completion of a 2-dose primary mRNA vaccine series during pregnancy was associated with a 61% decrease in COVID-19–related hospitalization among infants aged <6 months [ 26 ]. Furthermore, COVID-19 vaccine is safe and poses no additional risk to breastfeeding women or breastfed infants [ 27 , 28 ]. SARS-CoV-2–specific immunoglobulin G and immunoglobulin A antibodies have been shown to be present in breastmilk following vaccination of breastfeeding women, which could provide protection of infants should they be exposed to infection [ 29 , 30 ].…”
Section: Safety and Efficacy Of Covid-19 Vaccine In Pregnant Womenmentioning
confidence: 99%
“…In the United States, maternal completion of a 2-dose primary mRNA vaccine series during pregnancy was associated with a 61% decrease in COVID-19–related hospitalization among infants aged <6 months [ 26 ]. Furthermore, COVID-19 vaccine is safe and poses no additional risk to breastfeeding women or breastfed infants [ 27 , 28 ]. SARS-CoV-2–specific immunoglobulin G and immunoglobulin A antibodies have been shown to be present in breastmilk following vaccination of breastfeeding women, which could provide protection of infants should they be exposed to infection [ 29 , 30 ].…”
Section: Safety and Efficacy Of Covid-19 Vaccine In Pregnant Womenmentioning
confidence: 99%
“…A thorough search of the literature revealed that studies about heterologous vaccination schedules in lactating women and the effect on specific antibodies in human milk are lacking. In most studies with lactating women, researchers have reported the administration of at least one dose of the same vaccine (mRNA-based or vector-based; De Rose et al, 2022). However, the antibody response in serum was investigated in two observational cohort studies (Nordström et al, 2021; Normark et al, 2021) and two randomized controlled trials (Borobia et al, 2021; Sablerolles et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…53 A systematic review of 46 studies in pregnant and lactating patients showed no increased risk of adverse effects from COVID-19 vaccination. 54 Furthermore, data from multiple studies demonstrate that immunoglobulin G antibodies cross the placenta to protect the infant at birth (ie, are found in umbilical cord blood and neonatal blood) and are found in breast milk. The precise kinetics and durability of these antibodies are unknown.…”
Section: Vaccination In Special Populationsmentioning
confidence: 99%